Secure Data Sharing in Cloud Computing: A Comprehensive Review - Reddy P, Muthi; S. H., Manjula; K. R., Venugopal (International Journal of Computer (IJC), 2017)
Cloud Computing is an emerging technology, which relies on sharing computing resources. Sharing of data in the group is not secure as the cloud provider cannot be trusted. The fundamental dif?culties in distributed computing of cloud suppliers is Data Security, Sharing, Resource scheduling and Energy consumption. Key-Aggregate cryptosystem used to secure private/public data in the cloud. This key is consistent size aggregate for adaptable decisions of ciphertext in cloud storage. Virtual Machines (VMs) provisioning is effectively empowered the cloud suppliers to effectively use their accessible resources and get higher bene?ts. The most effective method to share information resources among the individuals from the group in distributed storage is secure, ?exible and ef?cient. Any data stored in different cloud data centers are corrupted, recovery using regenerative coding. Security is provided many techniques like Forward security, backward security, Key-Aggregate cryptosystem, Encryption and Re-encryption etc. The energy is reduced using Energy-Ef?cient Virtual Machines Scheduling in Multi-Tenant Data Centers.